MicroRNAs regulate critical genes associated with multiple myeloma pathogenesis - Pichiorri, Flavia; Suh, Sung-Suk; Ladetto, Marco; Kuehl, Michael; Palumbo, Tiziana; Drandi, Daniela; Taccioli, Cristian; Zanesi, Nicola; Alder, Hansjuerg; Hagan, John P; Munker, Reinhold; Volinia, Stefano; et al. (Proceedings of the National Academy of Sciences - PNAS, 2008)
Progress in understanding the biology of multiple myeloma (MM), a plasma cell malignancy, has been slow. The discovery of microRNAs (miRNAs), a class of small noncoding RNAs targeting multiple mRNAs, has revealed a new level of gene expression regulation. To determine whether miRNAs play a role in the malignant transformation of plasma cells (PCs), we have used both miRNA microarrays and quantitative real time PCR to profile miRNA expression in MM-derived cell lines (n = 49) and CD138+ bone marrow PCs from subjects with MM (n = 16), monoclonal gammopathy of undetermined significance (MGUS) (n = 6), and normal donors (n = 6). We identified overexpression of miR-21, miR-106b~25 cluster, miR-181a and b in MM and MGUS samples with respect to healthy PCs. Selective up-regulation of miR-32 and miR-17~92 cluster was identified in MM subjects and cell lines but not in MGUS subjects or healthy PCs. Furthermore, two miRNAs, miR-19a and 19b, that are part of the miR-17~92 cluster, were shown to down regulate expression of SOCS-1, a gene frequently silenced in MM that plays a critical role as inhibitor of IL-6 growth signaling. We also identified p300-CBP-associated factor, a gene involved in p53 regulation, as a bona fide target of the miR106b~25 cluster, miR-181a and b, and miR-32. Xenograft studies using human MM cell lines treated with miR-19a and b, and miR-181a and b antagonists resulted in significant suppression of tumor growth in nude mice. In summary, we have described a MM miRNA signature, which includes miRNAs that modulate the expression of proteins critical to myeloma pathogenesis.